Effect of omega-3 long-chain polyunsaturated fatty acid supplementation on heart rate: a meta-analysis of randomized controlled trials. Issue 6 (June 2018) - Hidayat, Khemayanto; Yang, Jing; Zhang, Zheng; Chen, Guo-Chong; Qin, Li-Qiang; Eggersdorfer, Manfred; Zhang, Weiguo
Abstract Background Elevated resting heart rate (HR) has emerged as a new risk factor for all-cause and cardiovascular mortality. The effect of marine-derived omega-3 long-chain polyunsaturated fatty acid (n−3 LCPUFAs) supplementation on HR was investigated as an outcome in many clinical trials. The present study was to provide an updated meta-analysis on the HR-slowing effect of n−3 LCPUFAs, and to differentiate the chronotropic effect between eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Methods PubMed and Cochrane databases were searched for relevant articles examining the effects of n−3 PUFAs on HR through May 2017. A random-effects model was used to generate the pooled effect sizes and 95% confidence intervals (CIs). The pooled effect sizes were presented as weighted mean differences (WMDs). Results A total of 51 randomized controlled trials (RCTs) with approximately 3000 participants were included in this meta-analysis. Compared to placebo, n−3 PUFA supplementation mildly but significantly reduced HR (−2.23 bpm; 95% CI: −3.07, −1.40 bpm). Moderate evidence of heterogeneity was observed among included trials (I 2  = 49.1%, P heterogeneity < 0.001). When DHA and EPA were separately administered, modest HR reduction was observed in trials that supplemented with DHA (−2.47 bpm; 95% CI: −3.47, −1.46 bpm), but not in trials with EPA. Conclusions The present meta-analysis provides strong clinical evidence demonstrating the effect of heart rate reduction by n−3 LCPUFA supplementation. When DHA or EPA administered alone, heart rate was slowed by DHA rather than by EPA.